What's wrong with the Philippine higher education?. - Tan, E. A.
Philippine higher education (HE) plays an important role in the countryÕs economy and is vital in achieving global competitiveness.Poor quality,undeveloped innovation system, and inequality of access caused the current dismal state of the HE system.This could be traceable to the populist education policy all past governments have adopted.Poor quality HE led to poor quality graduates, which lowered the productivity of the countryÕs labor force and inhibited technological progress. The Philippines then fell behind its East Asian neighbors in economic growth and social development. The paper recommends drastic reforms of the HE subsidy system from the ad hoc and politically based allocation toward a well-planned HE development program that addresses the above problems: quality improvement, development of an innovation system and an effective scholarship system.